Creating inclusive schools: Enhancing educational opportunities for migrant and refugee children in Ireland - Mc Guckin, Conor; Lynam, Aoife (Education Matters., 2024)
As Ireland sees an increasing number of migrant and refugee children entering its education system, the challenges and opportunities presented by this demographic shift are becoming more apparent. Migrant and refugee children, particularly those fleeing conflict, bring diverse cultural backgrounds and unique educational needs. This article examines the integration of migrant and refugee children into Ireland’s education system and proposes key strategies to enhance both academic and social inclusion.
Education matters: Ireland's yearbook of education 2024
PUBLISHED
Dublin, Ireland